The Influence Beyond Center and Circle Time Method t on Learning Discipline in Children Aged 5-6 Years Through Family Role Playing Centers in RA. Kesuma Elkaemde Namorambe - Fahdia; Juli Yanti Harahap (PT Inovasi Pratama Internasional, 2022)
This study aims to determine how much influence the beyond center circle time method has on learning discipline in children aged 5-6 years through the family role playing center at RA Kesuma Elkaemde Namo Rambe. This type of research is quantitative research (experimental) with a pre-experimental design, namely one group pretest-posttest. Collecting data using non-test, namely structured observation. The research sampling technique was purposive sampling, namely the sample in this study were children aged 5-6 years in group B, totaling 16 people consisting of 9 boys and 7 girls. The data analysis technique is descriptive analysis. The results of the research show that there is a significant effect of the beyond center and circle time method on the learning discipline of children aged 5-6 years. This is in accordance with the results of the hypothesis test Tcount> Ttable ( 4.009> 1.753) HO is rejected and Ha is accepted. That is, it can be concluded that there is a significant effect of the beyond center and circle time method on children's learning discipline in playing family roles.